Development of Behaviorism Learning Model in Fiqh Subjects in the Digital Era - Yulianisa Dewi Kunthi; Suwendi; Khoirunnisa Az-Zahra (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
In general, this study aims to analyze the relevance of behaviorism learning models in fiqh subjects and their development in the digital era. Based on the context of behaviorism theory, which emphasizes the formation of behavior through responses to stimuli. Thus, this study uses a library research method with a qualitative approach. The materials used were sourced from literature, primarily in the form of books and journal articles, particularly scientific journals with recent publications within the last five years. The results and discussion in this study show that (1) the principles of behaviorism learning have relevance to fiqh learning because it focuses on behavior changes that are observed as a benchmark for learning success. (2) There are behaviorism methods that can be applied to Fiqh learning, such as the lecture method, demonstration method, Drill or habituation method, and memorization method. (3) In its development in the digital era, teachers can use various digital technology media, such as learning applications, as stimuli and reinforcement. Thus, it is found that the implications for fiqh learning, such as creating interactive and innovative learning, (4) various previous studies have documented positive results from the application of behavioristic principles in religious education, especially in improving worship skills, discipline, and material retention. (5) There are various challenges in the implementation of Behavioristic Models in the Digital Context, limited access to technology, uneven quality of digital content, and the risk of decreased cognitive and spiritual depth due to too much focus on the repetition of external behaviors.